The effect of soil type on imazamox phytotoxicity to tomato - Gajic Umiljendic, Jelena; Sarić-Krsmanović, Marija; Šantrić, Ljiljana; Radivojević, Ljiljana (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2016)
A bioassay was performed to evaluate the susceptibility of tomato to imazamox residues in loamy and sandy soils. The effects of three different levels of soil moisture (20, 50 and 70% FWC) were also examined. Imazamox was applied at rates ranging from 6.25 to 800 μg a.i./kg soil. Shoot and root fresh weight and root length were the parameters measured 21 days after treatment, as well as the content of water soluble proteins.Imazamox caused growth delay and lower protein contents in both types of soil at all levels of soil moisture, and the degree of change depended on application rates. Inhibition was higher in plants grown in the sandy soil. The root parameters were more reliable as indicators of plant sensitivity to imazamox in soil. Soluble protein contents were lower in all trial variants but the changes did not depend on herbicide concentrations.
Keywords: Herbicides; Residues; Soils; Phytotoxicity; Tomatoes